Early Mortality of Brain Infarction Patients and Red Blood Cell Distribution Width - Lorente, Leonardo (Brain Sci, 2020)
Background: Meta-analysis has found that high baseline red blood cell distribution width (RDW) is associated with increased long-term mortality (mortality at one year or more) in ischemic stroke. The objectives of this study were to determine whether there is an association between RDW and 30-day mortality, and to explore whether RDW during the first week of ischemic stroke could be a 30-day mortality biomarker. Methods: We included patients with malignant middle cerebral artery infarction (MMCAI). RDW at days 1, 4, and 8 of MMCAI were determined. The end-point study was 30-day mortality. Results: We found that survivor (n = 37) in respect to non-survivor patients (n = 37) had lower RDW at days 1 (p < 0.001), 4 (p < 0.001), and 8 (p = 0.02). The area under curve (95% CI) for prediction of 30-day mortality by RDW at days 1, 4, and 8 of MMCAI were 0.80 (0.69–0.89; p < 0.001), 0.79 (0.66–0.89; p < 0.001), and 0.73 (0.58–0.84; p = 0.02). Regression analysis showed an association between RDW (odds ratio = 1.695; 95% CI = 1.230–2.335; p < 0.001) and 30-day mortality. Conclusions: The association between RDW and early mortality, and the potential role of RDW during the first week of MMCAI as a prognostic biomarker of early mortality were the main novelties of our study.